Prenatal ultrasound detection of fetal omphaloccle leading to diagnosis of a subtle unbalanced chromosome translocation: unbalanced chromosome: translocation, der(7) t (7p;9p): case report (to upload) - Ismail, Hamizah (2009)

(untitled)
Objective: Omphalocele is one of the most frequently encountered congenital anomalies during prenatal ultrasound. The heterogenous causes lead to an unpredictable prognosis and made genetic counseling difficult. Efforts to investigate the etiology pay off following uncovering a new chromosome rearrangement. Design: A 38 year old, G3P1SA1 Taiwanese lady, was expecting her second child. At 17 weeks, prenatal ultrasound discovered an isolated omphalocele. She received amniocentesis, result showed a male kryotype carrying a suspicious tiny terminal deletion at the distal short arm band of one chromosome 7:46,XY,del(7)(p22). FISH (fluorescence in situ hybridization) study using chromose 7p subtelomere probe (Vysis, Inc) confirmed losing a distal 7p signal. Meanwhile, both parents were urged for karyotyping to rule out malsegregation in a translocation heterozygote. The mother has normal chromosomes; the father's chromosomes, however, showed very subtle exchange of material on top of the short arms of one chromosome 7 and one chromosome 9, all very tiny pale stain areas. To further clarify the picture, array CGH (comparative genomic hybridization)-CMDX BAC aCGH CA2500 was ordered using DNA extracted from amniotic fluid back-up culture and the results released: 7p22.3p22.1 (RP11-90P13-RP11936A1)x1, 9p24.3p24.3(RP11-1112G-RP11-635C16)x3. The fetus ended up having a derivative chromose 7, resulting from a paternal reciprocal translocation between 7p and 9p that led to monosomy distal 7p and trisomy distal 9p: 46,XY,der97)t(7p22;9p24)pat. The couple opted for termination of pregnancy. Conclusion: This case demonstrated using molecular techniques, FISH and array CGH, help in dignosing subtle cytogenetic findings that add to the list of structural chromosomal abnormalities related omphalozale